PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DALAM MENINGKATKAN MOTIVASI DAN HASIL BELAJAR FISIKA MATERI GERAK MELINGKAR PADA SISWA KELAS X.B SMA NEGERI 1 SELEMADEG - I Ketut Sudiatmika (LP3M Universitas PGRI Mahadewa Indonesia, 2023)
Problem Based Learning is an innovative learning model that can provide active learning conditions to students through team or group learning. Motivation is a mental impulse towards individuals or people as members of society. This type of research is classroom action research. The research objective was to find out whether the application of the Problem Based Learning learning model could increase students' motivation and physics learning outcomes. The subjects in this study were students of class X.B SMA Negeri 1 Selemadeg in the even semester of the 2022/2023 academic year. The object of this research is the study of understanding circular motion material and students' responses to the problem-based learning model. This study uses two cycles and each cycle through four stages of the process (1) planning, (2) action, (3) observation, and (4) evaluation and reflection. If the problem of activities in one cycle has not been successful, it will be continued in the second cycle until the research conducted is declared successful. The results of the action research show that (1) the application of the problem-based learning model can improve the ability to answer circular motion questions, (2) there is positive student motivation towards the application of the problem-based learning model to improve the ability to answer questions.